2013
DOI: 10.2147/opth.s53397
|View full text |Cite
|
Sign up to set email alerts
|

Sensory exotropia due to keratoconus and review of the literature

Abstract: This case report describes a 17-year-old boy with sensory strabismus due to keratoconus and an ipsilateral nodular lesion of the bulbar conjunctiva. The aligned eye was the right eye and keratoconus in this eye was of late onset. Vision in the left eye was poor and keratoconus was advanced in this eye. Due to the longstanding nature of the keratoconus and its occurrence in a developmentally sensitive period, sensory exotropia had developed in the left eye. There was a nodular lesion of the bulbar conjunctiva i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Concerning post-traumatic strabismus, it has been reported that many etiologies play a role (vascular injury, orbital fracture, muscle rupture, head and face injury, and nerve injury), but it is a less common type of strabismus [ 31 33 ]. Some eye diseases, such as chorioretinal atrophy, congenital cataract, optic atrophy, retinal disease, complicated cataract, leukoma, coloboma, high myopia, congenital glaucoma, penetrating trauma, contusional eye trauma, and traumatic cataract cause visual impairment and may lead to strabismus by resulting in suppression [ 34 , 35 ]. In our study, the number of strabismus cases with epilepsy was 38 (9.7%), the number of those associated with trauma was 4 (1%), and the number of those associated with other ocular disorders was 14 (3.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning post-traumatic strabismus, it has been reported that many etiologies play a role (vascular injury, orbital fracture, muscle rupture, head and face injury, and nerve injury), but it is a less common type of strabismus [ 31 33 ]. Some eye diseases, such as chorioretinal atrophy, congenital cataract, optic atrophy, retinal disease, complicated cataract, leukoma, coloboma, high myopia, congenital glaucoma, penetrating trauma, contusional eye trauma, and traumatic cataract cause visual impairment and may lead to strabismus by resulting in suppression [ 34 , 35 ]. In our study, the number of strabismus cases with epilepsy was 38 (9.7%), the number of those associated with trauma was 4 (1%), and the number of those associated with other ocular disorders was 14 (3.6%).…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports of exotropia with keratoconus but no case of PMD has been reported to present with ocular deviation. Ciftci et al 7 reported a case of a boy of 17 years with advanced keratoconus, BCVA of 1/60, and exotropia of the eye. Sherafat et al 6 evaluated 350 patients with keratoconus and found that 20 of them had abnormal binocular function.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Sensory strabismus is a less common form of strabismus, the prevalence of which has been reported to be 5−9%. 7 Temporary or permanent loss of vision in one or both eyes can lead to sensory strabismus. We report a case of PMD and sensory exotropia in the background of VKC.…”
Section: Introductionmentioning
confidence: 99%